Posttraumatic growth in post-surgical coronary artery bypass graft patients. Issue 1 (9th February 2015) - Waight, Catherine A; Strodl, Esben; Sheridan, Judith; Tesar, Peter
Recent research in posttraumatic growth has been applied to people with life-threatening illnesses to optimise recovery. There is a lack of research exploring posttraumatic growth in coronary artery bypass graft patients. This article describes the recovery experience of 14 coronary artery bypass graft patients (13 males and 1 female) at their first outpatient review post-surgery. Grounded theory analysis was used to develop a model of distinct and shared pathways to growth depending on whether patients were symptomatic or asymptomatic pre-coronary artery bypass graft. Outcomes of posttraumatic growth in this sample included action-based healthy lifestyle growth and two forms of cognitive growth: appreciation of life and new possibilities. The model of posttraumatic growth developed in this study may be helpful in guiding future research into promoting posttraumatic growth and behaviour change in coronary artery bypass graft patients.